2022
DOI: 10.3390/metabo12030251
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity and NMR-Fingerprinting of Balkan Endemic Species Stachys thracica Davidov

Abstract: Stachys thracica Davidov is a Balkan endemic species distributed in Bulgaria, Greece, and Turkey. In Bulgaria, it is classified as “rare” and is under the protection of the Bulgarian biodiversity law. The aim of our study was to develop an efficient protocol for ex situ conservation of S. thracica and to perform comparative NMR-based metabolite profiling and bioactivity assays of extracts from in situ grown, in vitro cultivated, and ex vitro acclimated plants. Micropropagation of S. thracica was achieved by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 34 publications
3
14
0
Order By: Relevance
“… 47 1 H and 2D-NMR spectra of crude methanolic extract of Stachys thracica led to the unambiguous assignment of 15 individual compounds including VER. 48 In the present study, principal signals showing the 1 H resonances and principal homonuclear correlations obtained by 2D-COSY spectra have led to the assignment of the different moieties of VER in the ethanol extract on the basis of previously published compound assignments. 50 52 …”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“… 47 1 H and 2D-NMR spectra of crude methanolic extract of Stachys thracica led to the unambiguous assignment of 15 individual compounds including VER. 48 In the present study, principal signals showing the 1 H resonances and principal homonuclear correlations obtained by 2D-COSY spectra have led to the assignment of the different moieties of VER in the ethanol extract on the basis of previously published compound assignments. 50 52 …”
Section: Resultsmentioning
confidence: 65%
“…NMR analysis of crude extracts for confirming the presence of active polyphenols has been reported previously in several studies. 47 , 48 Zou et al utilized 1 H NMR to characterize the chemical profile of plant extracts of Cistanche deserticola and confirmed VER as one of the active marker compounds. 49 Confirmation by NMR of phenylethanoids (VER) has been reported earlier from Rydingia michauxii extracts.…”
Section: Resultsmentioning
confidence: 99%
“…In Achillea thracica and Veronica caucasica , 1 mg/L of BA stimulated growth under in vitro conditions, while in Verbascum eriophorum , 0.5 mg/L of BA stimulated the formation of 14.22 ± 0.2 shoots, without vitrification or callus formation being observed [ 23 , 24 , 25 ]. Panayotova et al [ 26 ] and Mantovska et al [ 11 ] reported the initiation of in vitro cultures of S. maritima and S. thracica where low seed germination was observed, but robust growth occurred on the medium without added growth regulators.…”
Section: Resultsmentioning
confidence: 99%
“…It has been successfully applied in the assessment of genetic diversity in natural populations of medicinal plant species from the Lamiaceae family like the Thymus species, Lavandula angustifolia , and Origanum vulgare [ 36 , 37 , 38 ]. SRAP analyses have been useful in the evaluation of genetic fidelity in in vitro cultivated plants like Passiflora edulis [ 39 ], and a recent report demonstrated the application of SRAP markers for confirming the genetic identity of in vitro and ex vitro adapted S. thracica plants [ 11 ]. In the current research, 16 combinations of SRAP primer pairs were used for the generation of fragments from S. scardica plant variants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation